DEVELOPING CALF (CONTEXTUAL, ATTRACTIVE, LOGICAL, AND FUN) MEDIA TO TEACH READING FOR YOUNG LEARNERS - Mahayanti, N. W. S. (International Journal of Language and Literature, 2017)
This study aims at developing media for group work activity in teaching reading for elementary school students. It was conducted in SD 4 Kaliuntu located in Buleleng. Observation sheets, teacher questionnaires, students’ questionnaires, and rubric were used to gain the data. Sugiyono’s R&D model was employed as the research procedures. The data obtained were quantitatively and qualitatively analyzed. From the result, it was found that the media could be developed by conducting several procedures, such as preliminary observation, syllabus analysis, library research, media development, experts’ judgment, and field test. Through those procedures, excellent prototype media named CALF were designed. As the implication, group work could be done effectively in that school setting.